The Growth and Yield of Rice (Oryza sativa L.) with Organic and Inorganic Fertilizer Application by Cellulolytic Microbes in Peat - Atrisina Allamah; Hapsoh Hapsoh; Wawan Wawan; Isna Rahma Dini (Talenta Publisher, 2018)
Limitations of productive land causing agricultural extension leads on marginal land. Peatlands are one type of land including the criteria for marginal land. Destruction of peatland ecosystems arising from land management and the selection of one commodity which is not in accordance with the characteristics of peatland. Damage criteria peat in government regulations to function cultivation is more than 0,4 m below the peat surface. One alternative for the agricultural development of peatlands associated with groundwater levels â‰¤0,4 m to do with the development of food crops, especially rice crops. This is because the root system of the rice crop is only about 40-50 cm categorized shallow roots, thus suitable for development on peatland shallow. This study aims to determine the response growth and yield of rice plants with organic and inorganic fertilizer application by microbial cellulolytic on peat soil. The experimental was conducted from November 2017 to January 2018 in Laboratory of Soil Science and Plant Laboratory, Faculty of Agriculture at Universitas of Riau. The research was conducted using a completely randomized design (CRD), which consists of 7 treatments and 4 replicates so on May 28 experimental units. As for the treatment Control, 50% inorganic fertilizer, 100% inorganic fertilizer, 80 grams of composted rice straw, 160 grams of litter rice straw + 160 ml consortium of microbes, 80 grams of composted rice straw + 50% inorganic fertilizer, 160 grams of rice straw litter + 160 ml of microbial consortium selulitik + 50% inorganic fertilizer. The results showed that addition of 160 g of rice straw litter + 160 ml of microbial + 50% inorganic fertilizer consortium was the best treatment by producing tillers reaching 54,87 tillers, the number of grain per panicle reached 130.57 grains with crop grain weight reaching 57.27 grams, with a percentage of empty the lowest is 3.62%.